Clinical Behavior of General Practitioners for Patients who Underwent an Operative or Conservative Treatment for a Craniocervical Fracture - Kalnev, Mihail; Uchikov, Petar; Kehayov, Ivo (Open Access Macedonian Journal of Medical Sciences, 2022)
Craniocervical fractures are socially important pathology. They represent one-third of the fractures in the cervical region. It is typical that elderly patients suffer from low-energy traumas such as falls, while younger patients suffer from high-energy traumas such as motor vehicle accidents, sport falls and etc. Craniocervical fractures are associated with an increased risk of craniocervical instability or neurological deficit. Primary therapeutic options depend on the type of fracture. Predictors of nonunions are the displacement of fractures, patients’ age, and comorbidities. The observership of the general practitioner in the postoperative period or the period of cervical immobilization could recognize possible malpositioning of the instrumentation, nonunion of the fracture, malsanation of the wound, and possible complications in case of the external immobilization. There is a lack of information on that topic. The goal of the paper is to summarise the most common fractures of the craniocervical region, their etiology, and treatment options and to present the results of our study of patients who underwent operative treatment for craniocervical fracture(s). Mastering the details, the treatment options, and the possible complication of the fractures in the craniocervical region, general practitioners could play an important role in the treatment of patients.